Effectiveness of dexmedetomidine in reducing blood loss during middle ear surgery under general anaesthesia: a randomized controlled trial - Sarkar, Chiranjib; Bhattacharyya, Chiranjib; Samal, Rajiv; De, Anisha; Bhar (Kundu), Sudeshna; Verma, Arvind Kumar; Pal, Suchismita (Journal of Society of Anesthesiologists of Nepal, 2016)
Background: Maintenance of relatively dry bloodless field is favoured by surgeons during middle ear surgery under operating microscope as it produces better visibility, ease of operation and reduces operating time. A highly selective alpha2 adrenergic agonist like dexmedetomidine, by virtue of its central sympatholytic, sedative and analgesic-sparing effect may provide such desired operating conditions. Methods: A randomised double-blind, placebo-controlled study was conducted to evaluate whether dexmedetomidine reduces blood loss in middle ear surgery under general anaesthesia and improve operative field visibility. Fifty-four patients aged 18-40 years, posted for elective middle ear surgeries were randomly divided into two groups. Patients of Group D (n=27) received dexmedetomidine in a loading dose of 1mcg/kg over 10 minutes before induction of anaesthesia followed by steady infusion at 0.4mcg/kg/hr. Group P (n=27) patients received corresponding volumes of normal saline as placebo. The operating surgeon assessed the intraoperative bleeding by a four-point Bleeding Score at the 10-minute interval and the Final Opinion on Bleeding Score at the end of surgery. For the test of statistical significance, a value of p less than 0.05 was chosen. Results: In Group D, the Bleeding Scores and the Final Opinion on Bleeding Score were significantly lower when compared with Group P (p < 0.05). Conclusions: Dexmedetomidine was found to significantly reduce intraoperative bleeding. This, in turn, improves operative field visibility and increases surgeon’s satisfaction during middle-ear surgery under general anaesthesia.